2002
DOI: 10.17796/jcpd.26.4.47n1670jr961x566
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric oral lesions: a 15-year review from São Paulo, Brazil

Abstract: There are few studies on pediatric oral pathologies in the literature. This study presents data from a review of 2,356 biopsies of young patients (birth to 14 years) received over 15 years (1985-2000) in the Oral Pathology Service at the University of Sao Paulo, Brazil. Information about patients (sex, age, race) and histopathological diagnosis was retrieved. Diagnosis data of 2,356 biopsies were classified into 20 groups.There was no significant difference between male (50.0%) and female (49.0%) patients. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
80
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 9 publications
28
80
1
7
Order By: Relevance
“…5,7,13,14,19,[22][23][24] Odontoma, also considered a frequent OT, was the third-most common lesion in our study. In some studies, it is shown to be the most frequent lesion, 5,6,12,22 although our study is more consistent with those conducted by Avelar et al, 18 Fernandes et al, 23 Jing et al, 19 Jones and Franklin, 9 Olgac et al, 14 Osterne et al, 13 and Saghravanian et al 15 in presenting an incidence of approximately 17%. Our study is in agreement with the data found in the literature that show a higher frequency in female patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…5,7,13,14,19,[22][23][24] Odontoma, also considered a frequent OT, was the third-most common lesion in our study. In some studies, it is shown to be the most frequent lesion, 5,6,12,22 although our study is more consistent with those conducted by Avelar et al, 18 Fernandes et al, 23 Jing et al, 19 Jones and Franklin, 9 Olgac et al, 14 Osterne et al, 13 and Saghravanian et al 15 in presenting an incidence of approximately 17%. Our study is in agreement with the data found in the literature that show a higher frequency in female patients.…”
Section: Discussionsupporting
confidence: 91%
“…OTs are lesions rarely observed in dentistry clinics, [5][6][7]9,12,13 and their frequency was 3% in our study, with a mean age of 30 years, varying between 5 and 75 years, and occurring more often in male patients. Their main location was in the posterior mandibular area.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In this study only adolescents were selected and all lesions that occurred were investigated and diagnosed by clinical and/or histopathological examination, whereas 49.46% of them were exclusively diagnosed by clinical examination. However most studies conclude their diagnosis based on the histopathological analysis (Chen et al, 1998;Sousa et al, 2002;Jones & Franklin;Dhanuthai et al, 2007;Wang et al).…”
Section: Discussionmentioning
confidence: 99%
“…Eighty percent of ameloblastomas present in the mandible of which 70 percent occur in the posterior molar region. [7][8][9] These lesions can be locally aggressive if left untreated and thus early diagnosis is vital to minimise the extent of surgery Aetiology is uncertain; it has however been suggested that they may arise in dentigerous cysts, within remnants of the dental lamina or the basal layer of the oral mucosal epithelium. 10,11 Suggested predisposing factors have included irritation in the form of extractions, caries, trauma, infection, tooth eruption, nutritional deficits and viral infection especially Human Papilloma Virus (HPV).…”
Section: Aetiologymentioning
confidence: 99%